Analysis of the Al-Muyassar Fi Ilmi Al-Nahwi Textbook and its Implications for Student Learning Outcomes - Amelya, Asy Syifa Reza; Tsani, Muhammad Jaohar; Ali, Mad; Kamilah, Dini (Universitas Yudharta Pasuruan, 2024)
Textbooks greatly support the success of students in achieving various knowledge competencies. However, many books do not meet the eligibility standards, causing problems, one of which is learning outcomes that do not reach the Minimum Completion Criteria. So, this study aims to analyze the eligibility aspects of the book Al-Muyassar Fī 'Ilmi Al-Naḥwi based on the Education Standards, Curriculum and Assessment Agency (BSKAP) eligibility standards and explain the impact of its use on student learning outcomes. The type of research used is qualitative-descriptive. The research design used is content analysis and observational studies. The research population was grade VIII students in one of the Madrasah Tsanawiyah in Bandung City. Participants were selected through a purposive sampling technique, and the result was that the sample that met the predetermined criteria amounted to 10 people. Data collection techniques consist of two kinds, namely test and non-test instruments. Data obtained will be processed with 3 stages of data analysis techniques: data reduction display and verification. Based on the review of the book of Al-Muyassar Fī 'Ilmi Al-Naḥwi based on the BSKAP standards, this book has mostly achieved the BSKAP standards that have been determined. However, the book of Al-Muyassar Fī 'Ilmi Al-Naḥwi has not played the maximum role it should because this book cannot be used independently by students, and the learning outcomes achieved are not optimal.